Dietary intake of patients with acne vulgaris in Karachi: an observational study - Badder Hina Afnan; Sadaf Ahmed Asim; Mehreen Amer; Sahar Soomro; Areesha Khan; Rabiya khan; Meeraal Kaikaus (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: The pathology of acne is vaguely understood to date, current epidemiologic evidence in Eastern populations indicates that consumption of chocolate, milk intake, fatty products, and glycemic load may be involved. Previously little research has been conducted highlighting the possible relationship between diet and acne among patients in Pakistan. The objective of this study was to identify the association of acne vulgaris and dietary intake patterns. METHODOLOGY: An observational study enrolled 246 participants, both genders, 16 to 40 years of age, diagnosed with Acne Vulgaris recruited from a tertiary-care hospital out-patient clinic in Karachi. The structured questionnaire consisted of various methods for assessing nutritional parameters. Statistical analysis was carried out using SPSS, the association of Acne was tested with dietary habits using Pearson-Chi Square test. Food items with a p-value less than 0.05 in the Chi Square test were considered in Binary logistic regression for estimating the risk for Acne with a 95% confidence interval (C.I.). RESULTS: Fifty-two percent of participants were found with mild acne, use of yogurt, ice cream butter, margarine, French fries, chocolate, bakery chips, white bread, vegetable, fruits, cake dates, and pickles give a significant association with severity of acne using Fisher’s Exact test p<0.05. Logistic regression showed that butter gave more risk for acne with an odds ratio of 1.11 and 95% C.I. (1.0, 9.2). CONCLUSION: It can be stated that dairy products, high glycemic index, and fatty foods are associated with acne aggravation in our population. As patients are always concerned about dietary advice, suggesting that they reduce these products would help them maintain their skin.